2023
DOI: 10.3350/cmh.2022.0342
|View full text |Cite
|
Sign up to set email alerts
|

Development of hepatocellular carcinoma in treated and untreated patients with chronic hepatitis B virus infection

Abstract: Hepatitis B virus (HBV) is responsible for more than 50% of hepatocellular carcinoma (HCC) in HBV hyperendemic areas like the Asia-Pacific region. Several hepatitis B viral factors are involved in HBV-related hepatocarcinogenesis. Hepatitis B viral load has been confirmed to be the most important risk factor of HCC development. In addition, HBV integration, HBV genotype C, core promoter mutations are also associated with risk of HCC development. For untreated chronic hepatitis B (CHB) patients, the estimated H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 142 publications
0
11
0
Order By: Relevance
“…The significance level was P=0.05, where P<0.05 indicated statistical difference. Platelet-albumin-bilirubin (PALBI) score was calculated as: 2.02 * log 10 bilirubin -0.37 * (log 10 bilirubin) 2 -0.04 * albumin -3.48 * log 10 platelets + 1.01 * (log 10 platelets) 2 , bilirubin was expressed in mmol/L, albumin in g/L and blood platelet count in 1000/mL. PALBI was divided into three grades, with higher grades indicating poorer liver function.…”
Section: Discussionmentioning
confidence: 99%
“…The significance level was P=0.05, where P<0.05 indicated statistical difference. Platelet-albumin-bilirubin (PALBI) score was calculated as: 2.02 * log 10 bilirubin -0.37 * (log 10 bilirubin) 2 -0.04 * albumin -3.48 * log 10 platelets + 1.01 * (log 10 platelets) 2 , bilirubin was expressed in mmol/L, albumin in g/L and blood platelet count in 1000/mL. PALBI was divided into three grades, with higher grades indicating poorer liver function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, current antiviral therapy for HBV cannot eradicate HBV. 55,56 In our cohort, most patients who did not receive antiviral therapy might have been included in the immune-tolerant phase or inactive carrier phase.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the fact that patients with advanced stage of CHB patients fulfill antiviral therapy indication. In addition, current antiviral therapy for HBV cannot eradicate HBV 55,56 . In our cohort, most patients who did not receive antiviral therapy might have been included in the immune‐tolerant phase or inactive carrier phase.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hepatitis B virus (HBV) infection is a major risk factor for the development of hepatocellular carcinoma (HCC) [ 1 ]. To ensure adequate HCC surveillance, several risk prediction models for HCC have been developed for patients with chronic HBV infection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent report suggested that treatment with BSV improves hepatic histology and decreases intrahepatic covalently closed circular DNA (cccDNA) [ 14 ]. Considering that hepatic necroinflammation, liver fibrosis, cirrhosis, and the persistence of cccDNA are associated with the development of HCC [ 1 , 15 ], the favorable effect of BSV on these factors may lower the risk of HCC in patients with CHB. However, to date, there are no data for the influence of BSV treatment on the occurrence of HCC.…”
Section: Introductionmentioning
confidence: 99%